Correlation between Psychological Distress and Coping Mechanism Strategy among Health Workers with Confirmed COVID-19 - Ruri Yuni Astari; Hera Hijriani; Lia Natalia (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2022)
Introduction: The COVID-19 pandemic has become a serious problem in the world of health that attacks the wider community or globally and has an impact in the form of psychological disorders among health workers as the forefront in the management of COVID-19; it is necessary for health workers with confirmed COVID-19 to have a coping mechanism strategy to overcome the problem of psychological distress. This study aims to determine the correlation between psychological distress and coping mechanism strategy among health workers with confirmed COVID-19.Methods: The quantitative descriptive method with a cross sectional approach was applied in this study which was conducted on June 3–July 2, 2021 and involved 129 health workers with confirmed COVID-19 in Majalengka District who were selected by incidental sampling technique. Data were collected through DASS-21 and BRIEF COPE questionnaires. Data analysis used frequency distribution, pearson correlation and multiple regression.Results: Based on this study, the highest score was obtained for the category of psychological distress (anxiety) is 43%, the coping mechanism strategy among health workers with confirmed COVID-19 was problem-focused coping by 2.95 and there was a significant correlation between psychological distress and coping mechanism strategy among health workers with confirmed COVID-19.Conclusions: Research result there was a significant correlation between psychological distress and coping mechanism strategys among health workers with confirmed COVID-19. Multidisciplinary interventions to deal with psychological problems in health workers are required to minimize the level of anxiety and stress they face.